2020
DOI: 10.36953/ecj.2020.21301
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioplastics and sustainable packaging materials from rice straw to eradicate stubble burning: A Mini-Review

Abstract: India is the second-largest producer of rice, which plays an important role in the GDP of the nation, but the burning of rice straw is one of the most severe issues, which the country is facing. The government has tightly regulated this practice, and the farmers are usually advised to incorporate the residue in the soil, but this management option is minimal because of its slow degradation properties in the soil and may also foster rice diseases. A lot of lab-scale and commercial research studies have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…Various research studies showed different statistics of crop residue generation (Table 1). It is quite challenging for farmers to manage substantial amount of stubble, which drags them to setting fire (Sain, 2020). Following are the most probable reasons of stubble burning in India:…”
Section: Root Cause For Stubble Burning In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Various research studies showed different statistics of crop residue generation (Table 1). It is quite challenging for farmers to manage substantial amount of stubble, which drags them to setting fire (Sain, 2020). Following are the most probable reasons of stubble burning in India:…”
Section: Root Cause For Stubble Burning In Indiamentioning
confidence: 99%
“…This technology is already in use in some paper mills, where it provides approximately 60 percent of the energy needed. Paddy straw is also used as a common raw material in the production of paper and pulp board (Sain, 2020). This management practice might somehow possibly be an alternative to deforestation.…”
Section: Management Of Crop Residuementioning
confidence: 99%
See 1 more Smart Citation
“…with a global annual production of 181.5 billion tons and energy value between 5 and 50 EJ/year (Kang et al, 2014;Maurya et al, 2015;Paul and Dutta, 2018). Conventionally, lignocellulosic biomass has been used for the production of biofuels, bioethanol, grafted polymers, platform chemicals apart from its unscientific burning which causes secondary environmental pollution (Bozell et al, 2011;Kang et al, 2014;Mukherjee et al, 2018;Zheng et al, 2014;Sain, 2020). With the advent of nanoscience and nanotechnology, a revolutionary concept, the lignocellulosic biomass has been utilized non-conventionally by its miniaturization to nano-scale (Lee et al, 2014;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable packaging materials are usually derived from lipids, polysaccharides, proteins or their combination and can also act as a barrier for moisture, gas, flavourings as well as lipid, which improve the food consistency by reducing its degradation and thereby enhancing its shelf stability. Biodegradable packaging is eradicated to synthetic plastic packaging (Sain, 2020).…”
Section: Introductionmentioning
confidence: 99%